AICCRA CSA-Bundle two Lesson Learned Workshop Report - Mudege, Netsayi; Kanyembo, Henry; Sichone, Mercy; Kakwasha, Keagan; Chileya, Agness; Muzungaire, Lizzy (WorldFish, 2023)
This report presents the outcome of the lessons learned workshop organized by WorldFish in partnership with the AICCRA CSA-Bundle two Accelerator partners working on integrated aquaculture-agriculture systems in Luapula and the Northern Provinces of Zambia. The main aim of the workshop was to reflect on the experiences, successes, challenges and outcomes of the project to identify valuable insights and takeaways to inform future work. The workshop was held at Sali’s Resort in Mansa on August 30th and 31st, August 2023, and 36 people (8 women) participated. The participants were drawn from the AICCRA accelerator partners, farmer cooperatives, the department of fisheries, commercial feed millers, and other private sector companies.